De la enseñanza de la lectura I. Global VS. Fonético: ¿Adivinar VS. Deletrear? - Luz Saldaña, M.; Sierra, Margarita; Lourdes Valenzuela, M.; Fernández, Gustavo (Revista Interamericana de Psicología/Interamerican Journal of Psychology, 2017)
Two methods of teaching reading, global and phonetic, are compared from the transfer perspective. The sample includes 16 children of the lower socioeconomic class from an experimental school in a working class neighborhood in Mexico City. It is concluded that neither of the two methods, in the form and condition employed, teach reading, although the phonetic method (spelling) teaches the sounding of letters and guarantees transfer to a certain extent, while the global method only permits the child to guess words. The percentage of word guessing was 72%. The possibility of definition of two levels of reading behavior is also discussed.